Policy and performance in Uganda's seed sector: Opportunities and challenges - Fredrick Bagamba; Proscovia R. Ntakyo; Geoffrey Otim; David J. Spielman; Bjorn Van Campenhout (John Wiley & Sons, Inc, 2022)
Motivation Efforts to increase smallholder access to improved varieties and quality seed is often central to agricultural development, economic growth, and poverty reduction in low-income countries. Yet many governments and development partners grow impatient with slow progress in their seed sectors. Uganda stands out for its recent policy innovations, regulatory reforms, and market experiments for seed, and for the extensive analysis of its experience. Purpose This article reviews the changing landscape of Uganda's seed system and assesses recent policy, regulatory, and institutional changes. Methods and approach We draw on a wide range of documents, studies, and statistics. Findings The low uptake of improved varieties and quality seed in Uganda has encouraged innovation to overcome failures in the country's seed market. These innovations include regulatory changes to allow the production of quality declared seed (QDS) by smallholder seed producers; labelling to allow text message verification of seed; and crowd-sourcing information on seed quality by farmers. All have promise, but it remains to be seen just how effective they will be. In the meantime, vested interests may resist moves to a more innovative seed sector, instead preferring to maintain the incumbent approach designed to use seed to secure political support from smallholders. This is at variance with the spirit of the 2018 legislation and subsequent regulatory reforms. Policy implications Uganda has a policy framework that could make a real difference to farmer access to better varieties and seed. Market innovations can help the vision to become reality. But the seed sector needs sufficient public investment to generate new varieties and foundation seed, and capacity to manage the seed market to the benefit of producers, dealers and farmers. Having come so far, it would be counter-productive for political economy factors to displace the efforts of private provision which is far more sustainable in the medium and long run.
Keywords: genetic resources policy; market development; seed policy; seed regulation; seed systems; Uganda